2xFe(+2y/x) -----> xFe(+3) +(3x-2y)e
3x-2y| S(+6)+2e->S(+4)
=>2FexOy+(6x-2y)H2So4-> xFe2(SO4)3 + (3x-2y) SO2+ (6x-2y)H20
Cái này đúng hơn nè. Câu dưới mik thay x,y là hoi sai
Phương trình hóa học:
\(2Fe_xO_y\)+\(\)(\(6\)\(x\)-\(2y\))\(H_2SO_4\)\(\rightarrow\)\(xFe_2\left(SO_4\right)_3\)+\(\)(\(3x\)-\(2y\))\(SO_2\)+(\(6x-2y\))\(H_2O\)
2FexOy +(6x-2y) H2SO4 \(\underrightarrow{T^o}\) xFe2(SO4)3+ (3x-2y)SO2\(\uparrow\) +(6x-2y)H2O
8Fe3O4 + 37H2SO4 = 12Fe2(SO4)3 + H2S + 36H2O
2FexOy +(6x-2y) H2SO4\(\underrightarrow{t^o}\) xFe2(SO4)3+ (3x-2y)H2S\(\uparrow\) + (6x-2y)H2O